ผลของปุ๋ยต่อการเติบโตของไผ่มันหมู - พวงจิก, ธัญพิสิษฐ์; อร่ามรัศมี, ชุดาภา; หาระโคตร, พรชัย (Thai Journal of Science and Technology, 2020)
The objective of this study was to examine the effects of chemical fertilizer on the growth rate of Dendrocalamus copelandii (Gamble ex Brandis) N.H.xIA & Stapleton) during November 2018 to May 2019, Treatments were compared between non-fertilizer (control) and 5 different chemical fertilizer applyings, i.e. 46-0-0 for 20 g/pot/time, 16-16-16 for 20 g/pot/time, 25-7-7 for 20 g/pot/time, 46-0-0 together with 25-7-7 for 10 g each/pot/time, and 16-16-16 together with 25-7-7 for 10 g each/pot/time. The trial was arranged in a completely randomized design (CRD), with 7 treatments and 3 replications, 2 pots per replication. The new shoot and culm diameter were recorded. Finally, electrical conductivity and pH values of growing media were analyzed. The results showed that the application of chemical fertilizer 46-0-0 together with 16-16-16 for 10 g each/pot/time promoted the highest number of new shoots. Moreover, the application of chemical fertilizer 16-16-16 together with 25-7-7 for 10 g each/pot/time resulted in the longest diameter.